Exploring the Biomechanical Properties of the Human Cornea In Vivo Based on Corvis ST - Zhang, Di; Zhang, Haixia; Tian, Lei; Zheng, Yan; Fu, Caiyun; Zhai, Changbin; Li, Lin (Frontiers in Bioengineering and Biotechnology, 2021)
Purpose: The aim of this study was to provide a method to determine corneal nonlinear viscoelastic properties based on the output data of corneal visualization Scheimpflug technology (Corvis ST). Methods: The Corvis ST data from 18 eyes of 12 healthy humans was collected. Based on the air-puff pressure and the corneal displacement from the Corvis ST test of normal human eyes, the work done by the air-puff attaining the whole corneal displacement was obtained. By applying a visco-hyperelastic strain energy density function of the cornea, in which the first-order Prony relaxation function and the first-order Ogden strain energy were employed, the corneal strain energy during Corvis ST test was calculated. Then the work done by the air-puff attaining the whole corneal displacement was completely regarded as the strain energy of the cornea. The identification of the nonlinear viscoelastic parameters was carried out by optimizing the sum of difference squares of the work and the strain energy using genetic algorithm. Results: The visco-hyperelastic model gave a good fit to the data of corneal strain energy with time during Corvis ST test (R2>0.95). The determined Ogden model parameter μ ranged from 0.42 to 0.74 MPa, and α ranged from 32.76 to 55.63. The parameter A and τ in the first-order Prony function were 0.09-0.36, and 1.21-1.95 ms, respectively. Conclusion: It is feasible to determine corneal nonlinear viscoelastic properties based on the corneal contour information and air-puff pressure of Corvis ST test.